PENGARUH CITRA MEREK (BRAND IMAGE) DAN KEPERCAYAAN MEREK (BRAND TRUST) TERHADAP KEPUTUSAN TOYOTA AVANZA DI KOTA SEMARANG - Trista, Nadia Lona; prihatini, Apriatni Endang; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2013)
Toyota is an automotive company that manufactures Toyota Avanza. There are several motives in buying the Toyota Avanza, one of which is the image of the brand. But, in the city of Semarang instability sales volume of Toyota Avanza. The purpose of this study was to determine the effect of brand image and brand trust on purchase decisions. The sampling technique used nonprobability sampling technique, purpose accidental sampling and purposive sampling-judgment sampling with a sample size of 100 respondents. Engineering analysis using linear regression analysis and correlation. The results of this study indicate that the variable brand image has positive and significant impact on purchasing decisions. The conclusion of this study is the image of the brand and trust in the brand Toyota Avanza is good. Suggestions can be submitted is a Toyota as a company should further strengthen the brand image and consumer confidence and sales of Toyota Avanza car will be more stable.